EFFECT OF UV INDUCED MUTATION ON AMYLASE PRODUCING POTENTIAL OF BACILLUS SUBTILIS (2620) - SURENDRA SINGH; VINNI SHARMA; MANOHAR LAL SONI; SHIPRA DAS SINHA (International Journal of Pharma and Bio Sciences, 2013)
The impact of ultra violet radiations on alpha amylase producing ability of Bacillus subtilis (2620) was studied. Maximum enzymatic activity (crude) upto 17 folds were obtained from mutant strain exposed to 60 minutes ultra violet irradiation in comparison to parent strain. Purified enzyme showed molecular weight of 68 KDa and 54 KDa by SDS-PAGE in both parent and mutant strains. The SDS-PAGE of mutant strain also showed the presence of other bands of higher molecular weight indicating the presence of additional proteins resulting due to UV exposure, leading to the higher production of amylase. Result of the Agarose gel electrophoresis of genomic DNA of parent and mutant strain showed that changes in the gene expression due to impact of UV does not change the genome of mutant strain of Bacillus subtilis